2018
DOI: 10.3390/cryst8090345
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Phase Transformation Analysis of Ni50−xTi50Lax Shape Memory Alloys

Abstract: The microstructure and martensitic transformation behavior of Ni50−xTi50Lax (x = 0.1, 0.3, 0.5, 0.7) shape memory alloys were investigated experimentally. Results show that the microstructure of Ni50−xTi50Lax alloys consists of a near-equiatomic TiNi matrix, LaNi precipitates, and Ti2Ni precipitates. With increasing La content, the amounts of LaNi and Ti2Ni precipitates demonstrate an increasing tendency. The martensitic transformation start temperature increases gradually with increasing La content. The Ni co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Although all these works try to fabricate metamaterials that can be applicable in multiple physical fields, a design of a meta-device that can not only work in multi-physical domains but also can automatically switch from one function to another as the environmental parameter changes, has still not been proposed. In this article, we try to solve the problem and provide a method to build such an intelligent bi-functional meta-device that can work in both thermal conduction and DC electric conduction situations by utilizing the shape memory alloys (SMAs) [29][30][31]. Due to its special lattice structure, owing to the solid-solid transition, the shape memory alloy (SMA) will switch from its original figure to a deformed figure as it is heated or cooled.…”
Section: Introductionmentioning
confidence: 99%
“…Although all these works try to fabricate metamaterials that can be applicable in multiple physical fields, a design of a meta-device that can not only work in multi-physical domains but also can automatically switch from one function to another as the environmental parameter changes, has still not been proposed. In this article, we try to solve the problem and provide a method to build such an intelligent bi-functional meta-device that can work in both thermal conduction and DC electric conduction situations by utilizing the shape memory alloys (SMAs) [29][30][31]. Due to its special lattice structure, owing to the solid-solid transition, the shape memory alloy (SMA) will switch from its original figure to a deformed figure as it is heated or cooled.…”
Section: Introductionmentioning
confidence: 99%
“…Martensite is the product of a diffusionless shear-like transformation. The papers published in this Special Issue [1][2][3][4][5][6][7][8][9] confirm that research in martensitic materials is very active. Even the old 'simple' Fe-C alloys keep many secrets that are still beyond the capabilities of modern computers.…”
mentioning
confidence: 53%
“…As mentioned previously, martensite is not restricted to steels; and other important martensitic materials are shape memory alloys. Li et al [7] have experimentally investigated the martensitic transformation of Ni 50−x Ti 50 La x alloys (x in the range 0.1 to 0.7). The Ms temperature increases gradually with increasing the La content, mainly because of the decrease of the Ni content in the equi-atomic matrix due to the formation of LaNi and Ti 2 Ni precipitates.…”
mentioning
confidence: 99%
“…Recently, some alloy systems have offered the possibility to produce in situ composites consisting of shape memory crystals and a glassy matrix [6][7][8][9]. Bulk metallic glass composites (BMGCs) can overcome the problems with BMGs using a transformation induced plasticity (TRIP) effect as loading [10][11][12][13]. Besides, in recent years, it has been found that the addition of rare earth elements can not only effectively improve the ability of amorphous formation, but also play an important role toward deoxidation, metamorphism, and strengthening alloys [14,15].…”
Section: Introductionmentioning
confidence: 99%